Molecular cloning and characterization of a distinct human phosphodiesterase gene family: PDE11A - Fawcett, Lindsay (The National Academy of Sciences, 2000)
We report here the cloning, expression, and characterization of human PDE11A1, a member of a distinct cyclic nucleotide phosphodiesterase (PDE) family. PDE11A exhibits ≤50% amino acid identity with the catalytic domains of all other PDEs, being most similar to PDE5, and has distinct biochemical properties. The human PDE11A1 cDNA isolated contains a complete open reading frame encoding a 490-amino acid enzyme with a predicted molecular mass of 55,786 Da. At the N terminus PDE11A1 has a single GAF domain homologous to that found in other signaling molecules, including PDE2, PDE5, PDE6, and PDE10, which constitutes a potential allosteric binding site for cGMP or another small ligand. Tissue distribution studies indicate that PDE11A mRNA occurs at highest levels in skeletal muscle, prostate, kidney, liver, pituitary, and salivary glands and testis. PDE11A is expressed as at least three major transcripts of ≈10.5, ≈8.5, and ≈6.0 kb, thus suggesting the existence of multiple subtypes. This possibility is further supported by the detection of three distinct proteins of ≈78, ≈65, and ≈56 kDa by Western blotting of human tissues for PDE11A isoforms. Recombinant human PDE11A1 hydrolyzes both cGMP and cAMP with K(m) values of 0.52 μM and 1.04 μM, respectively, and similar V(max) values. Therefore, PDE11A represents a dual-substrate PDE that may regulate both cGMP and cAMP under physiological conditions. PDE11A is sensitive to the nonselective PDE inhibitor 3-isobutyl-1-methylxanthine (IBMX) as well as zaprinast and dipyridamole, inhibitors that are generally considered relatively specific for the cGMP-selective PDEs, with IC(50) values of 49.8 μM, 12.0 μM, and 0.37 μM, respectively.